"No one cares": Challenges and possibilities for modernizing juvenile detention operations in mississippi. (16th September 2022) - Gulledge, Laura M.; Scheer, Charlie
Abstract: The status of Mississippi's juvenile corrections landscape was the focus of a 2018 federally‐funded study exploring the viability of a comprehensive database of statewide juvenile arrest data. Study findings indicated that the state's juvenile corrections infrastructure was primitive and incapable of sustaining such a database. However, promising elements were found to exist that may drive organizational changes at both the local and state level, and further innovations including adaptation of new technologies are also explored. Qualitative data from the pilot study reveals these indicators of potential change, which are then contrasted with theories on how organizational change can be conceived, implemented, and sustained. Implications for future research and practice are discussed.